PENERAPAN SANKSI PIDANA TERHADAP PELAKU KAMPANYE HITAM ( BLACK CAMPAIGN) PEMILIHAN KEPALA DAERAH DI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG INFORMASI DAN TEKNOLOGI - Merita, Enni; Afriani, Kinaria (Justici, 2023)
ABSTRACT Black campaigns carried out on social media such as Twitter or Facebook, etc., which contain insults and defamation of a certain pair of presidential and vice-presidential candidates, are prohibited acts as referred to in Article 27 paragraph (3) of Law Number 11 Year 2008 concerning Information and Electronic Transactions. The problem in this paper is how to apply criminal sanctions to black campaigners for Regional Head Elections on Social Media. In the framework of this writing, the authors conducted library research (library research). So that if it is related to the distribution of data in general, then what is used is secondary data. As for the criminal threat for those who fulfill the elements in Article 27 paragraph (3) of the ITE Law, they are subject to imprisonment for a maximum of 6 (six) years and/or a fine of up to Rp. 1,000,000,000.00 (one billion rupiah) .